(3GdMQjGJ GdYGeI aj GdacQ hGdfXGe GdSjGSj aj GdESdGe (B:s (3OQGSI ebGQfI (B/ s - (3YHO GdMcje MSf eMeO YHOGddgs; (3SdjeGf GdWeGhjs; (3LGeYI Yjf TeSs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb (B- (3LGeYI Yjf TeS,s, 1974)
(3CHQR GdHGMK SHb GdGSdGe aj JbQjQ GdMQjGJ GdYGeI hbGe HOQGSI ebGQfI ddMQjGJ habG ddacQ GdJbdjOj (B, (3hGdacQ GdGTJQGcj (B,((3GdeGQcSj haj GdOjebQGWjGJ GdTYHjI(B) , (3hadSaI GdGTJQGcjI GdYQHjI (B, (3Ke JWHjbGJgG aj GdfXe GdeYGUQI (B, (3Ke Hjf GdfXGe GdGSdGej (B, (3hadSaI GdMQjI ajg (B, (3heXGgQgG (B, (3hGdSjGOI (B,(3hGdeSGhGI (B, (3hMbhb GdeQCI (B, (3heQcR GdPejjf hfXGe GdQb hGdMQjGJ GdTNUjI (B, (3hfXGe GdQOI (B, (3hCfJgj Gdj HjGf VeGfGJ GdMQjGJ GdYGeI aj GdfXGe GdGSdGej ebGQfG HGdfXe GdENQj(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI Yjf TeS, cdjI GdMbhb, bSe GdbGfhf GdOSJhQj, (B1974.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 685-717 (3UaMIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdeUGOQ GdacQjIs; (3eOQSI GdbGfhf GdWHjYjs; (3GdacQ GdGTJQGcjs; (3GdeGQcSjIs; (3GdeSGhGI CeGe GdbGfhfs; (3GdMQjGJ GdaQOjIs; (3QSGFd LGeYjIs -- (3LGeYI Yjf TeSs